PENDAMPINGAN PROSES KREATIF DALAM MENULIS CERPEN MENGGUNAKAN BLOGSPOT PADA SISWA KELAS XI SMAN KABUH JOMBANG - Fitri Resti Wahyuniarti; Nanda Risky Ardhana; Amelia Septiana; Muhammad Saibani Wiyanto (Yayasan Nusantara Hasana Berdikari, 2025)
SMAN Kabuh offers significant opportunities in education, particularly in innovative and technologically adaptive learning processes. SMAN Kabuh, a state educational institution, has the potential for further development due to its excellent facilities and infrastructure. The short story writing learning process still uses traditional methods that do not utilize IT technology, such as Blogspot, which is easy to create and access for students. To develop students who can write short stories, this process approach prioritizes the writing process in its learning. These stages or processes are implemented to instill the principle of respecting the process undertaken by students until completion of their work. The creative process is more difficult than simply a seemingly effortless process. The stages of the creative process are: preparation, elaboration, illumination, and verification. The methods used in the community service activity, entitled